2021
DOI: 10.3389/fpsyg.2021.661427
|View full text |Cite
|
Sign up to set email alerts
|

How Inclusive Interactive Learning Environments Benefit Students Without Special Needs

Abstract: Growing evidence in recent years has led to an agreement on the importance and benefits that inclusive education has for students with special educational needs (SEN). However, the extension and universalization of an inclusive approach will also be enhanced with more evidence on the benefits that inclusion has for all students, including those without SEN. Based on the existing knowledge that learning interactions among diverse students are a key component of educational inclusion, the aim of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A starting point for this work is developing syllabi that challenge harmful paradigms within disciplines and highlight contributions from a diversity of scientists. Such efforts will encourage students and instructors in ecology, evolution, and allied fields to develop multiple historical perspectives and awareness of global issues, strengthen cultural consciousness and intercultural competence; combat prejudice and discrimination; and build social action skills that lead to change (Bennett, 2007 ; Molina Roldán et al, 2021 ; Sanger, 2020 ). Here, the authors (positionality shown in Box 1 ) propose a collaborative framework for educators to diversify their ecology and evolution syllabi.…”
Section: Why Diversify Classroom Content?mentioning
confidence: 99%
“…A starting point for this work is developing syllabi that challenge harmful paradigms within disciplines and highlight contributions from a diversity of scientists. Such efforts will encourage students and instructors in ecology, evolution, and allied fields to develop multiple historical perspectives and awareness of global issues, strengthen cultural consciousness and intercultural competence; combat prejudice and discrimination; and build social action skills that lead to change (Bennett, 2007 ; Molina Roldán et al, 2021 ; Sanger, 2020 ). Here, the authors (positionality shown in Box 1 ) propose a collaborative framework for educators to diversify their ecology and evolution syllabi.…”
Section: Why Diversify Classroom Content?mentioning
confidence: 99%
“…Thus, promoting education for responsible creativity means first and foremost training teachers in mindfulness, flow, mind wandering and ethics embodiment (Hagège, 2019) and focusing on new kinds of learning skills, such as psychosocial skills (e.g., creative thinking, regulation of emotions, regulation of stress, decision making, values ranking). Moreover, we know that school, family and classroom environments can influence children's academic performance, well-being, attention and social behavior (Day et al, 2015;Berman et al, 2018;Massonnié et al, 2019;Tapia-Fonllem et al, 2020;Molina Roldán et al, 2021).…”
Section: Redesigning Teacher Training and Classroom Environmentsmentioning
confidence: 99%
“…These interventions do not have a negative impact on children without disability, who are unaffected in their academic achievements when they learn in inclusive classrooms. This experience can also reduce prejudice towards people with disability and shape children and young people to be more accepting and supportive of people who are different from themselves (Molina Roldán et al, 2021 ). For example, the social effects of supported inclusion include reduction of fear, hostility, prejudice, and discrimination as well as increase of care, acceptance, and understanding (Kart & Kart, 2021 ).…”
Section: Introductionmentioning
confidence: 99%